Gross-total resection of temporal low grade gliomas is a critically important factor in achieving seizure-freedom - Meguins, Lucas Crociati; Adry, Rodrigo Antônio Rocha da Cruz; Silva Júnior, Sebastião Carlos da; Pereira, Carlos Umberto; Oliveira, Jean Gonçalves de; Morais, Dionei Freitas de; Araújo Filho, Gerardo Maria de; Marques, Lúcia Helena Neves (Arquivos de neuro-psiquiatria, 2015)
Objective To present a surgical series of patients with low grade temporal gliomas causing intractable epilepsy, focusing on long-term seizure outcome.Method A retrospective study was conducted with patients with temporal low-grade gliomas (LGG).Results Sixty five patients with were operated in our institution. Males were more affected than females and the mean age at surgery was 32.3 ± 8.4 (9-68 years). The mean age at seizure onset was 25.7 ± 9.2 (11-66 years). Seizure outcome was classified according with Engel classification. After one year of follow up, forty two patients (64.6%) were Engel I; seventeen (26.2%) Engel II; four (6.2%) Engel III and two (3.1%) Engel IV. Statistically significant difference in seizure outcome was obtained when comparing the extension of resection. Engel I was observed in 39 patients (69.6%) with total resection and in only 3 (33.3%) patients with partial resection.Conclusion Gross-total resection of temporal LGGs is a critically important factor in achieving seizure-freedom. Objetivo Apresentar uma série cirúrgica de pacientes com gliomas temporais de baixo grau, causando epilepsia de difícil controle.Método Estudo retrospectivo de pacientes com diagnóstico de glioma temporal de baixo grau temporais.Resultados 65 pacientes com foram operados em nossa instituição. A média de idade de início das crises foi de 25,7 ± 9,2 (11-66 anos). Após um ano de acompanhamento, quarenta e dois pacientes (64,6%) estavam Engel I; dezessete (26,2%) Engel II; quatro (6,2%) Engel III e dois (3,1%) Engel IV. Houve diferença estatisticamente significativa no resultado do controle das crises quando se compara a extensão da ressecção. Engel I foi observada em 39 pacientes (69,6%) com a ressecção total e em apenas 3 (33,3%) pacientes com ressecção parcial.Conclusão A ressecção total de glioma temporal de baixo grau temporais é um fator extremamente importante no controle das crises.